2021
DOI: 10.3390/diagnostics11020186
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Potential of Radiomics Features and Radiomics Signature from Pretherapeutic PSMA-PET-CT Scans and Clinical Data for Prediction of Overall Survival When Treated with 177Lu-PSMA

Abstract: Prostate-specific membrane antigen (PSMA) positron emission tomography/computed tomography (PSMA-PET/CT) scans can facilitate diagnosis and treatment of prostate disease. Radiomics signature (RS) is widely used for the analysis of overall survival (OS) in cancer diseases. This study aims at investigating the role of radiomics features (RFs) and RS from pretherapeutic gallium-68 (68Ga)-PSMA-PET/CT findings and patient-specific clinical parameters to analyze overall survival of prostate cancer (PC) patients when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…First of all, this examination is fast and non-invasive. Second of all, it could be used for therapy prediction and differentiation between low and high-risk patients [27] and for prediction of overall survival [20], as already published before. It could furthermore be the base of individual therapy and treatment tailoring in the future, combining the technique with analysis of textural parameters.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…First of all, this examination is fast and non-invasive. Second of all, it could be used for therapy prediction and differentiation between low and high-risk patients [27] and for prediction of overall survival [20], as already published before. It could furthermore be the base of individual therapy and treatment tailoring in the future, combining the technique with analysis of textural parameters.…”
Section: Discussionmentioning
confidence: 92%
“…A higher level of heterogeneity seems to predict a better response to PSMA therapy and may in the future allow a pre-therapeutic selection of responders to the treatment [19]. Moazemi et al have consecutively shown that these parameters also have prognostic potential for the overall survival of prostate cancer patients [20]. In summary, the software could take over and improve the whole process in the future, enabling specialists to focus on more important tasks.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Post-therapeutic SPECT, however, is not available prior to treatment and reliable outcome predictors before commencing PSMA-directed treatment would be desirable. As such, Moazemi et al investigated radiomic features from pretherapeutic [ 68 Ga]PSMA PETs and reported on the usefulness of such mathematically extracted scan signatures for outcome prediction in patients scheduled for [ 177 Lu]PSMA [ 27 ].…”
mentioning
confidence: 99%